An Indonesian Bilingual Child Development: Highlighting the Influential Factors and Strategies - Agis Andriani; Rika Kartika; Nita Sari Narulita Dewi; Edy Suroso (AL-ISHLAH: Jurnal Pendidikan, 2022)
Bilingual children are always interesting to be studied because they might have different uniqueness in experiencing their language development. Eleven years old Indonesian participant in this research experienced to have a special condition which makes her difficult to focus, but then, exposed to more than one language since she was a young age. Along with the proper parenting styles, this study gives empirical insight into the factors and strategies that contributed to maximising the children’s language development. Data were taken from observation of the video taken from the participant 3-4 years old until now, interviews with both the child and mother, and documentation showed that innate factors and strategies including watching and listening, imitating and repeating, storytelling and self-talking, doing minimal grasp strategy, code-switching and move-on strategies, and giving educational support and motivations are supported to the child to have the bilingual capacity in her communication. However, the milestone or stages of children’s bilingual development has not been investigated yet. Thus, to get a deeper understanding, future studies should investigate the milestone of children’s bilingual language development the findings can be extended to which could inform other researchers about what should be conducted next in the case that the longitudinal observation is needed.